Occurrence of blaTEM among Pseudomonas aeruginosa Strains Isolated from Different Clinical Samples in Erbil City - Sevan H. Bakir; Fattma A. Ali; Bashdar M. Hussen; Shahin H. Mustafa; Ahmed Akil; Shilan S. Ahmad (Polytechnic Journal)
Pseudomonas aeruginosa was a significant source of nosocomial infection with the presence of extended-spectrum β-lactamases (ESBLs) and metallo-β-lactamases (MBL) genes in P. aeruginosa being progressively documented globally. The purpose of this investigation was to detection the occurrence of MBL and ESBL in P. aeruginosa isolates acquired from diverse clinical samples, as well as the prevalence of blaTEM genes producing ESBLs. A total of 227 samples were obtained from various clinical specimens (wound, urine, sputum, bronchial wash, and burn) at public hospitals in Erbil region. Microorganism was obtained, treated, and recognized using normal microbiological culture procedures, biochemical testing, DNA extraction, and polymerase chain reaction to identify the presence of the blaTEM gene. Out of 227 specimens, 40 isolates (17.6%) were positive for P. aeruginosa, while 32 (80.6%) were considered as ESBL positive and 72.5% were positive for MBL manufacture by P. aeruginosa and the results of ESBL genes detection clarify that most of ESBL and MBL producer isolates of P. aeruginosa carried blaTEM gene which found in more than half (52.5%) of the isolates strains. The current study demonstrates that the development of MBL and ESBL in P. aeruginosa is increased and making these infections more challenging to cure. For the decrease of death rates and the propagation of multidrugresistant organisms by genes, early identification of MBL and ESBL synthesis is critical. As a result, a variety of measures must be used to control the spread of these diseases.